ANALYSIS OF INFLATION EFFECT ON INTEREST RATE SBI (PERIOD 2011-2017) - FAJAR ANDRE SAPUTRA (Jurnal Ilmiah Mahasiswa FEB, 2018)
Inflation is a very interesting economic phenomenon to be discussed,especially with regard to its broad impact on macroeconomic aggregates. 1), highdomestic inflation causes real rates of real domestic financial asset to be lower(and often negative), which can disrupt domestic fund mobilization and can evenreduce the domestic savings that are the source of investment funds. 2), can leadto reduced export competitiveness of goods and can lead to a deficit in the currentaccount and at the same time can increase foreign debt. 3), inflation canexacerbate the distribution of income by transferring resources from consumersand fixed income groups of producers. 4), high inflation may encourage capitalflight abroad. 5), high inflation will lead to a rise in the nominal interest rate thatcould disrupt the level of investment required to spur a certain level of economicgrowth (Hera Susanti et al., 1995). Based on the previous chapters of inflation affecting the SBI interest ratehence can be drawn conclusions and suggestions that can be used asconsideration. The conclusions and suggestions are as follows:The interest rate has a significant effect on inflation in the period 2011-2017 withthe resultant influence is positive. Uniform results will be used to increase interestrate.